Evaluating a new high-throughput twin-arginine translocase assay in bacteria for therapeutic applications - Ghosh, D. (Current Microbiology, 2017)
The twin-arginine translocase (Tat) pathway is involved in the transport of folded proteins in bacteria, and has been implicated in virulence and pathogenesis. A simple but efficient assay based on the quantification of the exopolysaccharide colanic acid was developed as a new means to study Tat function. Colanic acid contains a methylpentose (l-fucose) component, and its production is directly linked to the Tat pathway through the transport of enzymes involved in polysaccharide biosynthesis. Monitoring of l-fucose levels can be applied for identification of new Tat substrates and high-throughput screening of Tat inhibitors for therapeutic applications.